Three-Dimensional Texture Analysis Based on PET/CT Images to Distinguish Hepatocellular Carcinoma and Hepatic Lymphoma - Xu, Hanyue; Guo, Wen; Cui, Xiwei; Zhuo, Hongyu; Xiao, Yinan; Ou, Xuejin; Zhao, Yunuo; Zhang, Tao; Ma, Xuelei (Frontiers in Oncology, 2019)
Abstract: Objectives: This study compared the diagnostic ability of image-based and texture parameters in the differentiation of hepatocellular carcinoma (HCC) and hepatic lymphoma (HL) by positron emission tomography–computed tomography (PET/CT). Methods: Patients with pathological diagnosis of HCC and HL were included in this study. Image-based and texture parameters were obtained by manual drawing of region of interest. Receiver operating characteristic (ROC) was used to test the diagnostic capacity of each parameter. Binary logistic regression was used to transform the most discriminative image-based parameters, texture parameters and the combination of these parameters into three regression models. ROC was used to test the diagnostic capacity of these models. Result: Ninety-nine patients diagnosed to have HCC (n=76) and HL (n=23) by histological examination were included in this study (From 2011 to 2018, West China hospital). According to the AUC and p value, 2 image-based parameters and 5 texture parameters were selected. The diagnostic ability of texture-based model was higher than that of image-based model, and after combining those two groups of parameters the diagnostic capacity improved. Conclusion: Texture parameters can differentiate HCC from HL quantificationally, and can improve the diagnostic ability of image-based parameters.